Oxidative stress in pregnant women with diabetes mellitus - Roman V. Kapustin (Endocrinology Research Centre, 2017)
Oxidative stress (OS) plays an important role in embryo development, implantation, placentation, fetal development and labour. Diabetes mellitus (DM) is associated with an increase in OS processes. However, the expression of OS biomarkers in pregnant women with DM remains unclear. Based on a literature review, the features of the pro- and anti-oxidant systems of pregnant women with different types of DM have been established. Pregnancy in patients with DM has been shown to be characterised by an activation of OS processes. This leads to an overexpression of free radicals (peroxynitrite), toxic derivatives (malonic dialdehyde, 8-isoprostane) and specific enzymes (asymmetric dimethylarginine, catalase) and a decrease in the synthesis of antioxidants (superoxide dismutase, glutathione peroxidase and uric acid). The modified expression of these biomarkers is observed both in the blood and the placenta of pregnant women. These disorders can cause an unfavourable course of pregnancy, abnormal development of the placenta and development of adverse perinatal outcomes in pregnant women with DM. Nevertheless, given the inconsistency of data obtained, further scientific studies are needed to clarify this issue.